Contemporary art and capitalist modernization : a transregional perspective - Esanu, Octavian (New York : Routledge, 2021)
"This book addresses the art historical category of "contemporary art" from a transregional perspective, but unlike other volumes of its kind, it focuses in on non-Western instantiations of "the contemporary." The book concerns itself with the historical conditions in which a radically new mode of artistic production, distribution, and consumption - called "contemporary art" - emerged in some countries of Eastern Europe, the post-Soviet republics of the USSR, India, Latin America, and the Middle East, following both local and broader sociopolitical processes of modernization and neoliberalization. Its main argument is that one cannot fully engage with the idea of the "global contemporary" without also paying careful attention to the particular, local, and/or national symptoms of the contemporary condition. Part One is methodological and theoretical in scope, while Part Two is historical and documentary. For the latter, a number of case studies address the emergence of the category "contemporary art" in the context of Lebanon, Egypt, India, Hungary, Slovenia, Croatia, Bosnia and Herzegovina, Armenia, and Moldova. The book will be of interest to scholars working in art history, globalism, cultural studies, and postcolonial studies"--
Towards a historical understanding of post-Soviet presentism / Angela Harutyunyan -- Rabinec Studio : the commodification of art in late socialist Hungary, 1982-83 / Kristóf Nagyart -- Al-Nitaq festival of art, Cairo 2000 and 2001 / Dina A. Mohamed.
Includes bibliographical references and index.
Keywords: Art, Modern -- 20th century; Art and society -- History -- 20th century; Regionalism and the arts